Flow‐cytometric analysis of rare antigen‐specific T cells. Issue 8 (2nd August 2013) - Bacher, Petra; Scheffold, Alexander
Abstract : The cytometric enumeration and characterization of antigen‐specific lymphocytes, as introduced about 15 years ago, has contributed significantly to our understanding of adaptive immune responses in health and disease. Despite the development of several technologies, allowing to directly or indirectly analyze many aspects of lymphocyte specificity and function, several unresolved issues remain, due to the low frequency of certain antigen‐specific lymphocyte subsets and the complexity of T cell antigen recognition. This is especially true for CD4 + conventional as well as regulatory T cells, which bring major contributions to immune protection and pathology. Here we review the current technologies for the analysis of antigen specific T cells within the physiologic T cell repertoire and with a special focus on recent technologies addressing the analysis of rare antigen‐specific T cell populations including naive and regulatory T cells. © 2013 International Society for Advancement of Cytometry